P044 Ex vivo effects of infliximab on the long non-coding RNAs expression levels in Crohn′s disease. (30th January 2023) - Baldan-Martin, M; Rubín de Célix, C; Orejudo, M; Ortega, L; Fernández-Tomé, S; Soleto, I; Ramírez, C; Arroyo, R; Fernández, P; Santander, C; Moreno-Monteagudo, J A; Casanova, M J; et al.
Abstract: Background: In recent years, evidence shows that long non-coding RNAs (lncRNAs) are key regulators of gene transcription and play important roles in the pathogenesis of inflammatory bowel diseases. LncRNA are involved in regulation of intestinal epithelial cell apoptosis, cell-cell interactions, enhancing inflammation, among others. Biological therapies, which are considered the most potent for disease control, only benefit one-third of patients. For this reason, a deeper understanding regarding the mechanisms by which biological drugs elicit their effect on intestinal mucosal is needed. Hence, we aimed to unravel the ex vivo modulator effect of infliximab on the lncRNAs expression in intestinal biopsies from patients with Crohn′s Disease (CD). Methods: We performed an unbiased transcriptomic analysis of intestinal biopsies from the ileum and colon from 30 patients [active CD = 10, quiescent CD = 10, healthy controls (HC) = 10] to identify lncRNA differentially expressed in the setting of infliximab modulation (Figure 1). Endoscopic biopsies were cultured with or without infliximab, and the transcriptome was determined by stranded total-RNAseq (reagents from Illumina Inc.). We used different databases (Ensembl Biomart, RNAcentral and ToppGene) to search for non-annotated lncRNA information and data on the location (cellular component), biological process and molecular function of differentially expressed lncRNAs. Results: Transcriptomic results revealed a widespread dysregulation of lncRNAs in ileum biopsies from patients with active CD, quiescent CD and HC compared to the colon at baseline and after infliximab culture (Figure 2). These differentially expressed lncRNAs were enriched in such pathways as proliferation, apoptosis, migration, inflammatory response of fibroblasts, response to wounding, posttranscriptional regulation of inflammatory genes and activation of the mitogen-activated protein kinase signaling pathways. Regarding the effect of infliximab according to intestinal location, presence of disease and activity, no significant lncRNAs were identified in the different study comparatives. Conclusion: We have characterized the basal transcriptomic landscape of lncRNAs in patients with CD (active and quiescent) and HC both in ileum and left colon. However, we have not found differential lncRNA expression due to the effect of infliximab, suggesting that the location (ileum or colon) is more relevant when analyzing differences in lncRNA expression in the intestinal tissue.